Burnout and depression in medical interns: causes, impact of war and coping strategies - Ogorenko , V.V.; Mavropulo , T.K.; Borysova , I.S.; Shusterman, T.Y.; Nikolenko, A.Ye.; Plekhanova, T.M. (Medicni Perspektivi, 2025)
This article presents the findings of a study on the causes, impact of war and coping strategies for burnout and depression among medical interns. The study aimed to identify the factors contributing to burnout and depression in interns, the effects of war on these conditions, and respondents’ suggested strategies for managing them, to develop preventive and psychoeducational measures. The study involved 63 medical interns from the Dnipro State Medical University, undergoing training at the Department of Psychiatry, Narcology and Medical Psychology, and the Department of Pediatrics 3 and Neonatology. The interns were divided into two groups based on their specialty: "Psychiatry" (Group 1) – 31 individuals, and "Pediatrics" (Group 2) – 32 individuals. A psychodiagnostic method was employed, utilizing a custom-designed questionnaire inspired by a Medscape survey. The questionnaire focused on burnout and depression in medical interns during wartime and consisted of 21 questions structured into five clusters. The study revealed a high prevalence of symptoms of depression and burnout syndrome. Specifically, 51,6% of Group 1 and 56,3% of Group 2 reported such symptoms. War significantly impacted the psychological state of respondents, as reported by 67,7% of Group 1 and 96,9% of Group 2. Key factors included information overload, air raid alarms, and working with war-affected individuals. Female respondents were more likely to report a significant impact of war, while male respondents noted reduced attentiveness and irritability in workplace relationships. Approximately 22% of participants considered changing their profession due to burnout, with higher rates observed in Group 2 (34,4% versus 9,7%). The main coping strategies were communication with loved ones (68,3%) and creating a comfortable work environment (84,1%). However, some respondents, particularly from Group 1, resorted to isolation or psychoactive substance use (25,8%). Despite the prevalence of these issues, only 25,4% sought psychological help, with some avoiding disclosure due to stigma. The findings highlight the urgent need to develop targeted psychoeducational and preventive programs to address professional burnout and depression, particularly during wartime and in the post-war period.